Knowledge, perceptions and attitudes of university students regarding COVID-19, Cyprus - Middleton, Nicos; Tsioutis, Charalambos; Kolokotroni, Ourania; Heraclides, Alexandros; Theodosis-Nobelos, Panagiotis; Mamais, Irene; Pantelidou, Maria; Christaki, Eirini; Nikolopoulos, Georgios K.; Dietis, Nikolas (My University, 2021)
University students represent an active group with important implications in the novel coronavirus transmission. Elucidating their knowledge, attitudes and perceptions was important for customizing communication material and other information activities.
Keywords: Αttitude; Βiological sciences; Cyprus; Εmpathy; Judgment; Perception; Positive attitude; College students; Misconceptions; Sars-cov-2; Covid-19